Creación de bases de datos de exposición a agentes ambientales en Centroamérica. - Chaves-Arce, Jorge (Instituto Tecnológico de Costa Rica., 2006)
For many years the priorities in the field of health and safety in the workplace focused on accident prevention and management systems , however occupational exposure to various risk factors began to gain relevance. With a publication of the International Labour Organization (ILO ) called Safety in Numbers in 2003 in commemoration of the World Day for Safety and Health at Work, it became clear that the deaths associated with working only 19 % were accidents , the remaining 81 % had other causes and is precisely the occupational cancer with 32% the main cause of death among workers in the world. This project was developed within the framework of cooperation between the ITCR and the National University for Masters in Occupational Health within the Health and Work Programme for Central America ( SALTRA ) . Part of component 2.2. Exposure and endpoint information systems ( seven subprojects of health hazard and risk surveillance) of SALTRA program was to promote the CAREX ( carcinogenic exposure) methodology in other Central American countries and to establish as a pilot track of occupational exposures to environmental agents. As a result of the project it was possible to apply CAREX in Panama and Nicaragua , both in 2005 , although the results were ready in 2006 and then the CAREX Guatemala ended in 2009 . El Salvador and Honduras CAREX could not realize due to serious logistical problems. The CAREX methodology is being promoted by the World Health Organization to be applied in all countries of Latin America and the Caribbean. Regarding the creation of records of exposures to environmental agents in both Nicaragua and Costa Rica was determined to be feasible to have these records , however problems in both countries were taken at the political level with state institutions and ministries , the which made it impossible to implement the initiatives.
Proyecto de Investigación. Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Seguridad Laboral e Higiene Ambiental, 2006
Keywords: Viabilidad; Fuentes; Selección; Organización; Registros